The effect of organizational capital on tax avoidance with gender diversity and CEO overconfidence as moderator - Elia Rossa; Cahyadi Husadha (Jurnal Akuntansi Aktual, 2023)
AbstractThe number of companies that report losses to avoid taxes increases significantly. This becomes a concern of the government. The purpose of this study is to examine the effect of organizational capital on tax avoidance with gender diversity and CEO overconfidence as moderators. The samples used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2016-2021 through a purposive sampling method. This data is analyzed by using ordinary least squares (OLS) regression. The results indicate that organizational capital increases tax avoidance, and gender diversity affects organizational capital on tax avoidance, but CEO overconfidence does not affect the relationship between organizational capital on tax avoidance. This study shows that less confident CEOs tend to take less risk because they put companies’ long-term contingent risk at stake.AbstrakJumlah perusahaan yang melaporkan kerugian untuk menghindari pajak meningkat secara signifikan. Hal ini menjadi perhatian pemerintah. Tujuan dari studi ini adalah untuk memeriksa efek modal organisasi pada penghindaran pajak dengan keragaman gender dan kepercayaan diri eksekutif yang berlebihan (CEO overconfidence) sebagai moderator. Sampel yang digunakan dalam penelitian ini adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (IDX) selama 2016-2021 melalui metode sampling khusus. Data ini dianalisis dengan menggunakan regresi persegi terendah biasa (OLS). Hasilnya menunjukkan bahwa modal organisasi meningkatkan penghindaran pajak, dan keanekaragaman gender mempengaruhi modal organisasi terhadap penghindaran pajak, tetapi kepercayaan diri eksekutif yang berlebihan tidak mempengaruhi hubungan antara modal organisasi dengan penghindaran pajak. Studi ini menunjukkan bahwa CEO yang kurang percaya diri cenderung mengambil risiko yang lebih sedikit karena mereka mempertaruhkan risiko kontinjensi jangka panjang perusahaan.